A comparative study of photocatalytic degradation of the antibiotic cefazolin by suspended and immobilized TiO2 nanoparticles. Issue 27 (8th June 2016) - Shokri, Mohammad; Isapour, Ghodsieh; Behnajady, Mohammad A.; Dorosti, Samaneh
Abstract: In this study, the photodegradation of cefazolin was investigated in the presence of suspended and immobilized TiO2 on a glass plate. The effects of the operational parameters such as the catalyst dosage for the suspended system, the initial pH of the solution, the initial concentration of the cefazolin, and light intensity were examined and compared in both systems. Scanning electron microscopy and atomic force microscopy were used to determine the surface properties of the immobilized catalyst on glass. The favorable conditions obtained for the photodegradation of cefazolin were pH 5, light intensity = 17 W m −2, and [cefazolin]0  = 20 mg L −1 in both the systems. Also, in the slurry system, the most suitable catalyst dosage was 400 mg L −1 . The kinetic examination, following the pseudo-first-order reaction kinetics, was made based on the Langmuir–Hinshelwood model.